Spacecraft electromagnetic compatibility technologies - Zhang, Hua; Zhang, Yuting; Huang, Chengbo; Yuan, Yanxing; Cheng, Lili (Springer, 2020)
This book explores key techniques and methods in electromagnetic compatibility management, analysis, design, improvement and test verification for spacecraft. The first part introduces the general EMC technology of spacecraft, the electromagnetic interference control method and management of electromagnetic compatibility. The second part discusses the EMC prediction analysis technique and its application in spacecraft, while the third presents the EMC design of spacecraft modules and typical equipment. The final two parts address spacecraft magnetic design testing technologies and spacecraft testing technologies. The book also covers the program control test process, the special power control unit (PCU), electric propulsion, PIM test and multipaction testing for spacecraft, making it a valuable resource for researchers and engineers alike.- Resumé vydavatele
Keywords: elektromagnetická kompatibilita; kosmické lodi; kosmická technika; electromagnetic compatibility; spacecraft; space technology; elektronické knihy; kolektivní monografie; electronic books; collective monographs